Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. Role of strategic management in developing administrative competence of employees in Islamic banks in Tulkarm Governorate Mahmoud Hasan Hejazi 2. The Impact of High-Performance Work Systems on Confrontation Competitive Challenges and The Role of Managerial Control as Moderating Variable in The Banking System at Dongola Locality in The Northern State of Sudan Mashair Hussien Khalifa Ali, Mahmoud AbdelMoati Hashem AbdelHamid 3. The impact of non-oil economic determinants on Saudi economic growth Abu Al-Qasim Abbas Mohammed 4. The effectiveness of the mechanisms for implementing the rules of international humanitarian law in Palestine Muamar Ali Orabi Nakhlah 5. The Impact of Macroeconomic Policies on Foreign Direct Investment in Sudan (1990-2020) Ebtihaj Hashim Mohammad Algzoli 6. Withdrawal Arguments and Their Applications in Iraqi Personal Status Courts Nadia Ali Hassan 7. Humanitarian and Weapons of Mass Destruction International Humanitarian Law Tahani Ahmed Ali